Antitumor Activity of ?-glucan Extracted from Pleurotus Eryngii - Ali Z. Al-Saffar1 , Noora A. Hadi2 , Hadeel Mohamed Khalaf3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pleurotus eryngii, a type of edible mushroom that exhibit various pharmacological properties, including antioxidant and anticancer effects. In the present study, extracted ?-glucan from the P. eryngii was tested as an antioxidant and anti-tumor factor. ?-glucan was extracted and analyzed by HPLC and FT-IR. Analytical results showed more than 90% similarity in chemical structure and purity. Potential antioxidant activity of ?-glucan was examined using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and compared with ascorbic acid.?- glucan confirmed a potential scavenging activity. The anticancer activity of the?-glucan was assessed using different concentrations (6.25 to 400 µgmL-1) on MCF-7 and HepG2 cell lines. P. eryngii?-glucan exerted a dose-dependent reduction in MCF-7 and HepG2 cell viability with an IC50 of 280.00 and 539.5 µg mL-1, respectively. At the same time, no significant effect was recorded on normal cell line WRL 68. The obtained results are expected that could be used to develop P. eryngii?-glucanas an antitumor drug